The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1055/s-0035-1563397
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Anastomoses Using End-to-End versus End-to-Side Technique in Lower Extremity Free Tissue Transfer

Abstract: No advantage was noted for ETE or ETS arterial anastomoses based on reconstructive outcomes. The choice of anastomotic technique in lower extremity free tissue transfer should be based on patient factors and the clinical circumstances encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
2
32
0
1
Order By: Relevance
“…By dissecting the artery up to its origin, an adequate vessel length and diameter can be achieved with a wide arc of rotation, which enables us to cover more distant defects around the knee and proximal/middle third of the lower extremity despite short‐pedicled free flaps. Moreover, dissection is straightforward and has a relatively low morbidity comparable to other reports in the literature (Cho et al, , Kang, Chung, Chang, & Kim, ). A difficult popliteal dissection can be avoided using our approach, as that area is an alternate recipient site around the knee.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…By dissecting the artery up to its origin, an adequate vessel length and diameter can be achieved with a wide arc of rotation, which enables us to cover more distant defects around the knee and proximal/middle third of the lower extremity despite short‐pedicled free flaps. Moreover, dissection is straightforward and has a relatively low morbidity comparable to other reports in the literature (Cho et al, , Kang, Chung, Chang, & Kim, ). A difficult popliteal dissection can be avoided using our approach, as that area is an alternate recipient site around the knee.…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, it has been reported that thrombus formation occurred more often in ETS anastomosis than in ETE anastomosis (Threlfall, ). Conversely, other studies have shown that there is no difference for ETE or ETS arterial anastomoses based on reconstructive outcomes (Cho et al, ). A recent study by Cho et al compared the reconstructive outcomes of lower extremity free flaps with ETE and ETS arterial anastomoses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…If a defect in the lower extremity cannot be reconstructed with a skin graft, the choice of defect reconstruction will favor local flaps and free tissue transfers. [1][2][3][4][5] In appropriate cases, skin graft and local flaps can be well tolerated by both patients and surgeons. However, lower limb defects need to be reconstructed using free flaps, and suitable vessels need to be present in the same extremity.…”
mentioning
confidence: 99%